2019
DOI: 10.1186/s12884-019-2198-6
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a peer-led antenatal breastfeeding class for fathers: perceptions of facilitators and participants

Abstract: BackgroundThe Parent Infant Feeding Initiative (PIFI) was a factorial, randomised controlled trial that aimed to prolong exclusive breastfeeding by targeting expecting fathers. One of the intervention strategies evaluated was a father-focused breastfeeding class facilitated by a male peer facilitator. The aim of this mixed-methods descriptive study was to 1) evaluate the feedback provided from participants of the class and 2) explore the motivations and experiences of volunteer male peer facilitators trained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…To our knowledge, PIFI is the largest breastfeeding intervention targeting fathers. We have previously reported on the process evaluation of the interventions and demonstrated that each interventions in terms of intent, content, and delivery was feasible, useful, and acceptable to fathers [ 34 , 39 , 50 ]. We were, however, unable to demonstrate impact of a face-to-face or mHealth intervention, either individually or in combination, on infant feeding outcomes, maternal breastfeeding self-efficacy, or level of postpartum partner support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, PIFI is the largest breastfeeding intervention targeting fathers. We have previously reported on the process evaluation of the interventions and demonstrated that each interventions in terms of intent, content, and delivery was feasible, useful, and acceptable to fathers [ 34 , 39 , 50 ]. We were, however, unable to demonstrate impact of a face-to-face or mHealth intervention, either individually or in combination, on infant feeding outcomes, maternal breastfeeding self-efficacy, or level of postpartum partner support.…”
Section: Discussionmentioning
confidence: 99%
“…Building on the feedback from participants and lessons learned in FIFI, we refined and updated the content of the FFABC, and 117 FFABCs with an average size of 4 to 6 participants were delivered by a team of 11 trained peer facilitators [ 39 ]. A short process evaluation survey was completed by 98% of class attendees, and overall satisfaction with class format, facilitation, and content was high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Informational-social support is social support that the family provides to the mother to support exclusive breastfeeding success. A study that provides father-focused antenatal breastfeeding interventions to fathers shows that fathers who provide education to mothers are better prepared to support mothers in exclusive breastfeeding [21].…”
Section: Discussionmentioning
confidence: 99%